2020
DOI: 10.3389/fonc.2020.01711
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetry and Feasibility Studies of Volumetric Modulated Arc Therapy With Deep Inspiration Breath-Hold Using Optical Surface Management System for Left-Sided Breast Cancer Patients

Abstract: Background: During radiotherapy (RT) procedure of breast cancer, portions of the heart and lung will receive some radiation dose, which may result in acute and late toxicities. In the current study, we report the experience of our single institution with organs at risk (OARs)-sparing RT with deep inspiration breath hold (DIBH) using an Optical Surface Management System (OSMS) and compare the dosimetric parameters with that of free breathing (FB). Patients and Methods: Forty-eight cases diagnosed as early stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 46 publications
(61 reference statements)
0
12
0
Order By: Relevance
“…DIHB VMAT planning showed a reduction from 5.4 to 3.6 Gy of MHD, and D2% to the heart was reduced from 19.3 to 13.4 Gy compared to VMAT-free breath (FB-VMAT) treatment plans. In the case of LADA, the average value of Dmean was also reduced from 6.9 to 3.9 Gy, and D2% was reduced from 19.5 to 9 Gy by using the DIHB technique associated with VMAT left breast irradiation ( 64 , 65 ).…”
Section: Strategies To Limit Heart Dose Irradiation: Deep Inspiration...mentioning
confidence: 99%
“…DIHB VMAT planning showed a reduction from 5.4 to 3.6 Gy of MHD, and D2% to the heart was reduced from 19.3 to 13.4 Gy compared to VMAT-free breath (FB-VMAT) treatment plans. In the case of LADA, the average value of Dmean was also reduced from 6.9 to 3.9 Gy, and D2% was reduced from 19.5 to 9 Gy by using the DIHB technique associated with VMAT left breast irradiation ( 64 , 65 ).…”
Section: Strategies To Limit Heart Dose Irradiation: Deep Inspiration...mentioning
confidence: 99%
“…75,79 Recently, the DIBH treatment using volumetric-modulated arc therapy (VMAT) is utilized for a patient with the left-sided breast cancer to irradiate both whole breast and regional node with superior target coverage and good cardiac sparing. 80,81 Fassi et al investigated target position reproducibility in the left-sided breast irradiation with DIBH using multiple optical control points. They compared the performance of optical surface imaging with that of the RPM-based methods and showed that the use of multiple surface fiducials leads to improved target and surface reproducibility.…”
Section: Breath-holdmentioning
confidence: 99%
“… 75 , 79 Recently, the DIBH treatment using volumetric-modulated arc therapy (VMAT) is utilized for a patient with the left-sided breast cancer to irradiate both whole breast and regional node with superior target coverage and good cardiac sparing. 80 , 81 …”
Section: Motion Monitoring Techniques In Breast Cancer Rtmentioning
confidence: 99%
“…Patients undergoing mediastinal radiotherapy for lymphoma have a risk of serious radiation-associated late toxicities such as cardiovascular disease and secondary cancers [2] . It was, hypothesised that this patient group could benefit from the use of a deep inspirational breath-hold (DIBH) technique, which has been previously implemented in breast cancer treatment, achieving heart sparing, as well as reduced lung toxicity [3] .…”
Section: Introductionmentioning
confidence: 99%